(untitled) (Journal of Nepal Geological Society, 2006)
The Bishnumati River, a major tributary of the Bagmati River in the Kathmandu basin, suffers from bank erosion, river instability, and environmental degradation. These processes are responsible for the loss of sediments, modification of river morphology, loss of vegetative buffer zone, and deterioration of stream environment. Bank erosion hazard in the Bishnumati River was assessed at ten different reaches using bank height ratio, ratio of riparian vegetation rooting depth to bank height, rooting density percentage, bank slope, and bank surface protection. Vertical and lateral stability of the river was assessed at four reference segments, namely at Bishnumatigaun, Okhaltar, Mahadevtar, and Tamsipakha, respectively from upstream to downstream. The riverbanks in the Bishnumatigaun segment show fluctuating trends of bank erosion potential from upstream to downstream. All the four segments of the Bishnumati River are vertically unstable and all the segments except the Okhaltar are entrenched. The Tamsipakha and Okhaltar segments have a high risk of lateral shifting, as they possess high values of bank erosion hazard index, meandering width ratio, and width-depth ratio. The Bishnumati river is in a degrading condition and capable of eroding sediments. The main causes of river instability are the excavation of river sediments, encroachment on riverbanks, clearing of riparian vegetation, and canalization.